Effective mineralization of quinoline and bio-treated coking wastewater by catalytic ozonation using CuFe2O4/Sepiolite catalyst: Efficiency and mechanism. (July 2019) - Liu, Dan; Wang, Chunrong; Song, Yifan; Wei, Yanhong; He, Lei; Lan, Bangrui; He, Xuwen; Wang, Jianbing
Abstract: In this study, CuFe2 O4 nanocomposite loaded on natural sepiolite (CuFe2 O4 /SEP) was prepared by the citrate sol-gel method. CuFe2 O4 /SEP was characterized by X-ray diffraction, Brunauer-Emmett-Teller adsorption analysis, scanning electron microscopy, and energy dispersive spectroscopy. The CuFe2 O4 /SEP composite was stable and showed an excellent catalytic activity for ozonation. The efficiency of quinoline mineralization in the catalytic ozonation with CuFe2 O4 /SEP was 90.3%, and this value was 5.4 times higher than that of the uncatalyzed ozonation (16.8%). The quinoline mineralization followed a pseudo first-order kinetics with all the catalysts. The rate constant for the mineralization of quinoline by ozonation in the presence of CuFe2 O4 /SEP was 0.0885 min −1, which was 16.7 times higher than that in ozone alone (0.0053 min −1 ). Radical scavenging tests revealed that hydroxyl radical (OH) and superoxide radical (O2 − ) were the reactive oxygen species (ROS) in the quinoline degradation. In the presence of CuFe2 O4 /SEP, ozone and hydrogen peroxide were rapidly converted into the ROS. Although neutral and alkaline pH were more beneficial for the quinoline mineralization, CuFe2 O4 /SEP exhibited significant catalytic activity even under acidic conditions. Meanwhile, five-cycle successive tests suggested that CuFe2 O4 /SEP was recyclable and hence, stable. Furthermore, the feasibility of the catalytic ozonation for the treatment of biologically treated coking wastewater was evaluated. The catalytic ozonation resulted in 57.81% total organic carbon removal efficiency at 60 min, which was 2.9 times higher than that in the uncatalyzed ozonation (19.99%). Graphical abstract: Image 1 Highlights: CuFe2 O4 /SEP was successfully synthesized by citrate sol-gel method. Quinoline mineralization by CuFe2 O4 /SEP + O3 (90.3%) was 5.4 times higher than O3 . CuFe2 O4 /SEP could enhance the decomposition of O3 to generate .OH and O2 − . CuFe2 O4 /SEP was effective in catalytic ozonation of bio-treated coking wastewater.